Haemoptysis in an intravenous drug user: injection needle impacted in the left main bronchus. (16th April 2014) - Shah, Asif R; Smyth, Louise; Tolan, Michael; Bartosik, Waldemar
Abstract : We report a case of a 35-year-old man who presented with 4-week history of haemoptysis, with a history of intravenous drug use. There was no other significant medical or surgical history and no recollection of any foreign body aspiration. Chest X-ray and CT scan showed 40 mm long needle in left main bronchus, partly lying outside the bronchus into the mediastinum. Flexible and rigid bronchoscopes proved to be unsuccessful in retrieving the needle. We proceeded with left posterolateral thoracotomy and the left main bronchus was explored to take out this 21-gauge (green) injection needle. The distal half of the needle with the sharp end was lying in the mediastinum piercing through the bronchial wall. Surgery was uneventful with good postoperative recovery and the patient was discharged 4 days later.